The Effect of Leadership and Performance of The Head of Madrasah on Teacher Work Motivation at Mts - Saiful Akhyar Lubis; Yusnaili Budianti; Wardani Sihaloho (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
This study aims to describe the influence of the leadership and performance of the madrasa principal on the work motivation of teachers at MTs Darul Hikmah, Sirandorung District, Central Tapanuli Regency. Used in this research is quantitative research with a descriptive approach. The descriptive approach is a method that describes or provides an overview of the object under study through data or samples that have been collected as they are, without conducting analysis and making generally accepted conclusions. Sources of data used are primary data and secondary data. Data collection techniques used include questionnaires and documentation. The data analysis technique used is classical assumption test, hypothesis testing, and multiple linear regression test. The results showed that the leadership and performance of the Madrasah Principal had a positive and significant effect on Teacher Work Motivation at MTs Darul Hikmah, Sirandorung District, Central Tapanuli Regency. This is shown by the results of the SPSS test, which shows that the leadership and performance of the Madrasah Principal affect teacher work motivation, which is 70.3%, other factors influence the remaining 29.7%.